The mind which knows Itself – does it salute its own twin? Augustine’s de Trinitate - Kurlavičiūtė, Gintarė (Religija ir kultūra, 2015)
[full article and abstract in Lithuanian; abstract in English]This paper focuses on Augustine’s account of self-knowledge, with a particular reference to De Trinitate. One of its main peculiarities is that self-knowledge (notitia sui), self-love (amor sui) and the mind (mens) are constructed as a mental triad. It is claimed that this scheme revolves around some incompatible assumptions as fautes de mieux. Self-knowledge is brought into play as a separate ontological unit: not only as an accident but also as a substance. At the same time, mind and self-knowledge are considered as concepts that can be reduced into one ontological unit. It is suggested that the symbiosis of these different ways of consideration could be inspired by Augustine’s attempt to cancel via analogiae between the corporeal and intelligible realms of reality.
Keywords: Augustine; mind; self-knowledge; self-love